2019
DOI: 10.1038/s42004-019-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free electrocatalysts for oxygen reduction reaction based on trioxotriangulene

Abstract: Development of a structurally well-defined small molecule with a high oxygen reduction reaction catalytic activity is a key approach for the bottom-up design of a metal-free carbonbased catalysts for metal-air batteries and fuel cells. In this paper, we characterize the oxygen reduction reaction activities of trioxotriangulene derivatives, which are stable neutral radicals with high redox abilities, via rotating disk electrode measurements in alkaline aqueous solution. Among trioxotriangulene derivatives havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…In addition, the recent theoretical study by Bredas and co-workers suggested that 2D π-conjugated covalent organic frameworks composed of TOT possess a high potential to exhibit intriguing electrical/magnetic properties [ 68 ]. We are currently continuing to research these new unconventional materials, including an application for a molecular catalyst [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the recent theoretical study by Bredas and co-workers suggested that 2D π-conjugated covalent organic frameworks composed of TOT possess a high potential to exhibit intriguing electrical/magnetic properties [ 68 ]. We are currently continuing to research these new unconventional materials, including an application for a molecular catalyst [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trioxotriangulene ( TOT 1 , Scheme 1 ) is a fused-polycyclic hydrocarbon [ 39 , 40 ] functionalized with three oxo-groups, and its neutral radical is highly stable even without steric protections due to the delocalization of electronic-spin [ 41 ]. Our recent investigation revealed various intriguing physical properties and functions of TOT derivatives based on the redox activity and self-assembling ability by π-stacking [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. We also demonstrated that TOT exhibits a four-stage redox ability from neutral radical to radical tetraanion species.…”
Section: Introductionmentioning
confidence: 99%
“…There are many strategies for the preparation of transition metal electrocatalysts explored [14][15][16] since Jasinski [17] reported for the first time in 1964 that cobalt phthalocyanine exhibited oxygen reduction activity. In the realm of heterogeneous catalysis, nano-carbon materials (porous carbon, graphene, carbon nanotubes, carbon fibers) and non-metallic (N, P, S) doped nanocarbon materials are widely used as catalysts and catalyst carriers [18][19][20]. As the carrier of an Fe-based electrocatalyst, carbon material plays a prominent role in further inhibiting the agglomeration of nanoparticles [21], providing more catalytic active sites, and facilitating the O 2 activation [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The oxo-substitution of the triangulene core endows the neutral trioxotriangulene (TOT) radical derived from 2 with chemical stability. This stabilization allowed the exploration of the rich redox properties of TOTs, 6 which can store up to four electrons reversibly, and the use of this system as a molecular component of cathode-active materials in organic batteries. The tri- tert -butyl TOT exhibited a high discharge capacity of more than 300 A h kg –1 , exceeding those delivered by Li-ion batteries.…”
mentioning
confidence: 99%